Design and Analysis of Power Head Axial Servo Loading System - Xianjin Shi; Hongqi Liu; Gang Sun; Baochao Wang (Institute of Advanced Engineering and Science, 2013)
Power head is the main motive mechanism of rotary drilling rig. High axial pressure and high frequency is one of its typical working conditions. Axial loading test is a key point in power head performance tests. Overall design, system theoretical analysis and simulation of power head axial loading system were carried out. The bond graph model and state equations of power head axial servo loading system were built on the basis of bond graph theory. Hydraulic system simulation model was constructed and axial steady-state and dynamic loading simulation was made by use of hydraulic simulation software. The maximum axial steady-state load is up to 450kN and the dynamic frequency is 20Hz, both of which can meet the technical requirements. The simulation validates the feasibility of the scheme about power head axial loading system and it provides theory and practice guidance for perfecting the loading system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3390